Modellin and Measuring the Alienation Feeling in the Ahvaz Urban Space - Maryam azadbakht; Saeed Amanpour; Mustafa mohammadi; Mojtaba Jahanifar (توسعه اجتماعی, 2024)
The material and spiritual separation of citizens from urban spaces creates an alienation feeling from the city. In this research, an attempt has been made to identify different dimensions of alienation feeling in urban spaces. This research has a practical purpose, and the sequential exploratory mixed method, with the grounded theory approach. In the qualitative phase, the basic components of the alienation feeling were extracted, and a conceptual model of alienation feeling in space was presented. Then, with the hierarchical confirmatory factor analysis, the collected data were fitted with the conceptual structure. Ahvaz citizens was used for the research population, and with stratified sampling, 610 Ahvaz citizens participated. The presented conceptual model is defined by five factors: the attachment to space feeling, the ineffectiveness of space feeling, the liveliness in space feeling, the space insecurity feeling, and the lack of identity in space feeling. Quantitative results showed that the proposed model has a good fit with the experimental data and its structural validity is favourable. The analysis of gender multiple groups showed that structural coefficients and correlation coefficients work differently for women and men. Researchers consider it strategic and useful to conceptualize the alienation feeling in the urban space in a multi-dimensional way, which is based on a lack of identity, insecurity, inefficiency, and lack of vitality, and they advise urban planners to consider this feeling and its causal factors and pay attention to the context of its creation in the urban space design and metropolitan policies.